Hand-assisted robotic right donor nephrectomy in patient with total situs inversus: A case report. (2016) - Gonzalez-Heredia, Raquel; Garcia-Roca, Raquel; Benedetti, Enrico
Highlights: "Total situs inversus" is an infrequent congenital condition. The robot has been already proved as a safe and attractive approach for living donor nephrectomies. "Total situs inversus" presents the surgeon with a challenging situation. In these cases, preoperative planning is essential. This is the first robotic right donor nephrectomy in a patient with total situs inversus. Abstract: Total situs inversus" is an infrequent congenital condition. The robot has been already proved as a safe and attractive approach for living donor nephrectomies. We report here the first right donor nephrectomy in a patient with total situs inversus that is performed using the Da Vinci platform.